Redefinition Of The Nasakh In The Modern Era (Study Of Zahrah Al-Tafâsîr By Abu Zahrah) - Idris, Mhd (Jurnal Ilmiah Ilmu Ushuluddin, 2023)
The discourse on the concept of nâsikh mansûkh is still controversial and still hot to talk about. This has become a prolonged polemic among scholars until now. The majority of scholars think that there are mansukh verses in the Qur'an. However, some scholars reject the textual concept of verses in the Qur'an. Among them is Abu Zahrah who emphasized that there is not a single verse in the Al-Qur'an that is transcribed. Therefore this research aims to find out Abu Zahrah's views and methods in understanding verses that are considered mansûkh by the majority of scholars and how it is applied in interpreting these verses in Zahrah al-Tafâsîr's book of Tafsir. This research is library research. The primary source of this research is the book Zahrah al-Tafâsîr by Abu Zahrah and related studies as secondary sources. The approach used in this research is the science of interpretation approach and the character study approach. Meanwhile, to process and analyze the data in this study, the content analysis method was used. The results of this study indicate that Abu Zahrah is one of the modern scholars who deny the existence of texts on verses of the Qur'an. The method used to complete the verses that appear contradictory is the al-taufiq (compromising) method. One of the forms among the texts that appear to be contradictory outwardly applies specifically, while the other applies in general so that the special one is the general one. The second form is interpreting one of the texts when meeting other arguments that support its interpretation. This is evidenced in interpreting the verses considered mansukhby the majority of scholars.